Construction Innovation. - Orstavik, Finn (Innovation in the built environment., 2015)
An edited book for academics, senior students and practitioners combining global theoretical and practice-based perspectives on innovation within the construction industry. Examines innovation from different positions and through different conceptual lenses to reveal the richness that the theoretical perspectives offer to our understanding of the way that the construction sector actors innovate at both project and organizational levels. Brings together leading scholars to deconstruct the concept of innovation and to discuss the merits of different perspectives, their commonalities and their d.